Ascomycetes with cellulolytic, amylolytic, pectinolytic, and mannanolytic activities inhabiting dead beech (Fagus crenata) trees - Fujii, K; Sugimura, T; Nakatake, K (Folia microbiologica, 2010)
It is generally accepted that dead tree decomposition is performed mainly by delignifying basidiomycetes. While ascomycetes have been reported to inhabit dead tree bark, their contribution to dead tree decomposition is still unclear. Here, we isolated five bark-inhabiting ascomycetes possessing cellulolytic activity from dead beech tree and assessed their polysaccharolytic activities. When cultivated in a medium containing filter paper as a sole carbon source, three strains degraded >40 % of the filter paper in a 4-week cultivation and the others degraded 15-30 % of the paper. The degraders possessed amylolytic, pectinolytic, and mannanolytic activities as well as cellulolytic activity, implying that they play an important role in dead tree decomposition after delignification by basidiomycetes. Phylogenetic analysis based on large subunit ribosomal DNA (lsu-DNA) sequences implied that the isolates belonged to Penicillium or Amorphotheca.
Keywords: buk (rod); Ascomycota; Sequence Analysis, DNA; papír; Genes, rRNA; pektiny; DNA fungální; Paper; fungální RNA; Amylose; DNA, Ribosomal; amylosa; Environmental Microbiology; geny rRNA; Pectins; Cellulose; Mannans; Fagus; mikrobiologie životního prostředí; DNA, Fungal; ribozomální DNA; celulosa; kultivační média; sekvenční analýza DNA; mannany; RNA ribozomální; RNA, Fungal; RNA, Ribosomal; Culture Media